Analysis Peak Hour Time of Highest Vehicle Volume on Several Roads in The East Surabaya Roads Area - Aulia Dewi Fatikasari; Achmad Dzulfiqar Alfiansyah; Rikky Sofyan Rizal (Nusantara Science and Technology Proceedings, 2023)
The East Surabaya area is one of the industrial and office centers. The high activity of the people in the city of Surabaya will affect transportation mobility which is marked by the growth of road traffic volume which continues to increase rapidly. This area has a lot of community mobility to and from the East Surabaya area. This caused congestion on several roads. Congestion is the main problem of transportation in urban areas. At certain hours there is often a spike in traffic volume that exceeds the capacity of existing roads. This is related to the starting hours of activities in East Surabaya and the ending hours of activities from East Surabaya which coincide, causing traffic jams. The East Surabaya area is divided into two times when the traffic volume increases, namely morning and evening. Based on this, this study aims to determine when there is a spike in traffic volume. The method used is a traffic volume survey, looking for peak hour volume based on cur/hour units and determining when peak hours occur. The results showed that the highest volume in direction 1 during peak hour occurred on Friday in Jalan Panjang Jiwo with a volume of 5947 cur/hour and direction 2 occurred on Friday on Jalan Jemursari. The average time for an increase in traffic volume in the East Surabaya area in the morning is 07.00 to 08.35 and in the afternoon is 15.35-18.00.